SOCIOECONOMIC SURVEYS FOR URBAN DEVELOPMENT AND WATER PROJECTS a guidebook - ASIAN DEVELOPMENT BANK ([S.l.]: ASIAN DEVELOPMENT BANK, 2022)
Provides practical tips and resources for conducting quality socioeconomic surveys to enhance the effectiveness of urban development and water projects. This guidebook explains the importance of high-quality socioeconomic surveys to strengthen project design, ensure robust due diligence, and inform evidence-based policies.
In English.
P.B
Keywords: Social Economic